Preparation and physical properties of calcium pectinate films modified with sunflower wax - Baumler, Erica Raquel (2014)
In this study, the preparation of films made from calcium pectinate (CP) and sunflower waxes (SFW) by casting is described. The optical properties, water resistance, thermal behavior, and rheological properties of SFW/CP films were examined. At higher SFW content irregular surfaces were obtained. Films made from a 2% aqueous pectin solution (PA) showed the best inclusion of the lipid material. Compared to SFW-free films, SFW/CP films were less transparent, being the SFW concentration the responsible for the loss of transparency. The swelling index was affected by SFW inclusion and PA concentration. In general, water adsorption was not affected by SFW concentration, but it was affected by the environmental conditions. The inclusion of SFW did not improve the moisture barrier efficiency of the films. The thermal behavior of SFW/CP films revealed a melting peak in the range of 70–80°C attributed to the melting of SFW. The rheological analysis showed G′ values between 2.98 × 105 and 71.9 × 105 Pa for films stored at lower water activities, and they ranged from 3.07 × 105 to 38.4 × 105 Pa at higher environmental humidity. In both cases, G′ values were affected by SFW inclusion. A linear viscoelastic region (LVR) was observed for all the samples.